Use of kraft lignin as compatibilizer in wood flour-polypropylene Composites - Rabi Behroz (Regional Information Center for Science and Technology (RICeST), 2011)
Effect of Kraft lignin as a compatibilizer on the short-term water absorption (2 and 24 hours) and mechanical properties of wood flour-polypropylene composites was studied. The black liquor of Chooka pulp and paper mill was acidified and Kraft lignin was extracted by precipitation.  The extracted lignin at three levels of 2, 5 and 10 percent was mixed with wood flour by physical mixing method. All materials used were oven-dried. Wood flour, lignin and PP with or without MAPP were used to produce composites by flat hot press method. The results of this study indicated that generally lignin improved physical (short term water absorption) and mechanical properties (flexural modulus, flexural strength and impact strength). The bending test result showed that without MAPP, the composites with 2 and 10 percent lignin exhibited higher flexural modulus and strength, respectively. But at the presence of compatibilizer, the composites with 5 percent lignin exhibited the highest flexural modulus and strength. The composite with 2 percent of lignin exhibited higher flexural modulus and short-term water absorption rather than the composites with 2% MAPP. This result indicated positive effect of lignin in the composites. Also the composites with 10 percent lignin exhibited the highest impact strength and short-term water absorption. But there were no significant difference between the impact strength of composites with 5 and 10 percent lignin.